Exposure to PM10 and lung function among welders of metal working factory in Selangor - Aziz, Nur Aida; Jalaludin, Juliana (School of Health Sciences, Universiti Sains Malaysia, 2014)
Welding is one of the key components of numerous metal-working industries, and its fume has potential physical and chemical health hazards. Several evidences from previous scientific studies have shown that welding fumes contain particles to which the exposure can affect lung function of the welders. The aim of this study is to determine the personal exposure to PM10 and lung functions, as well as respiratory symptoms among welders of a metal working factory with office workers as the comparative group. This study involved 33 welders and 43 office workers. Purposive sampling method was used to recruit respondents, and those who fulfilled the inclusion criteria were selected. A set of questionnaire adopted from American Thoracic Society was used to collect information on socio-demographic data and respiratory symptoms. Personal exposure to PM10 was measured using portable air sampling pump GilAir-5 (Sensidyn, U.S.A) and lung function test was performed using spirometer Chestgraph HI-101 (Chest M.I Inc., Tokyo). The exposure of PM10 for the welders were 4 times higher (471.6 μg/m3 (343.9)) as compared to the non-exposed group (121.1 g/m3 (6.3)). There were significant differences in FVC (litre) (p = 0.03), FEV1 (litre) (p = 0.02), FVC% (p = 0.02) and FEV1% (p < 0.001) between the welders and the non-exposed group. The numbers of reported respiratory symptoms were significantly higher among welders and logistic regression showed that exposure to PM10 increased the risk of chronic cough. The welding fume was found to be a factor contributing to significant risk of chronic cough, chronic phlegm and chest tightness after adjusted for smoking status. It is suggested that welders are highly exposed to PM10 compared to non-exposed, and there is an increased risk of exposure to their respiratory health.